2014
DOI: 10.1007/s00125-014-3343-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite signatures of exercise training in human skeletal muscle relate to mitochondrial remodelling and cardiometabolic fitness

Abstract: Aims/hypothesis Targeted metabolomic and transcriptomic approaches were used to evaluate the relationship between skeletal muscle metabolite signatures, gene expression profiles and clinical outcomes in response to various exercise training interventions. We hypothesised that changes in mitochondrial metabolic intermediates would predict improvements in clinical risk factors, thereby offering novel insights into potential mechanisms. Methods Subjects at risk of metabolic disease were randomised to six months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
134
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(148 citation statements)
references
References 25 publications
14
134
0
Order By: Relevance
“…In obese persons who have lost weight, multiple compensatory mechanisms encouraging weight gain have been evidenced to persist for at least 1 year. More precisely, there is a decrease in hormones which reduce the drive to eat (leptin, Peptide YY, Amylin, cholecystokinin) and an increase in the orexigenic hormone ghrelin associated with a rise in appetite as well as increased fasting and postprandial ratings of hunger and desire to eat [37].…”
Section: Discussionmentioning
confidence: 99%
“…In obese persons who have lost weight, multiple compensatory mechanisms encouraging weight gain have been evidenced to persist for at least 1 year. More precisely, there is a decrease in hormones which reduce the drive to eat (leptin, Peptide YY, Amylin, cholecystokinin) and an increase in the orexigenic hormone ghrelin associated with a rise in appetite as well as increased fasting and postprandial ratings of hunger and desire to eat [37].…”
Section: Discussionmentioning
confidence: 99%
“…This discovery of interindividual response to low-intensity exercise prompted us to further examine skeletal muscle gene expression after stratification of the IGT cohort based on the normalization of blood glucose levels during an OGTT after the exercise intervention. Although the effects of various exercise training regimens on gene expression profiles in skeletal muscle have been assessed (19,(23)(24)(25)(26)(27)(28), comparatively limited information is available on the adaptive response to exercise training in people at risk for developing type 2 diabetes (29). We have taken a focused approach to gain insight into the molecular "fingerprint" associated with the early indications of IGT and the adaptive response to low-intensity unsupervised exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this study focused on free fatty acids, acylcarnitines and a subset of amino acids. More recently, the same group employed a larger, targeted metabolomics platform in skeletal muscle biopsies in an expanded sample, and found that a high amount of vigorous intensity aerobic exercise significantly increased concentrations of even-, medium-, and long-chain acylcarnitines, while resistance training and a low-amount of vigorous intensity aerobic exercise preferentially increased short- and medium-chain acylcarnitines (17). …”
Section: Introductionmentioning
confidence: 99%